2016
DOI: 10.1080/10498850.2015.1036482
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Quality of Refined Fish Oil in an Accelerated Storage Study

Abstract: The aim of this study was to prepare the refined oil derived from Sardinella longiceps by a stepwise procedure of degumming, bleaching, and deodorization. The refined sardine oil showed greater susceptibility towards oxidation than the crude oil, but the addition of ethyl acetate fractions of the red seaweeds Hypnea musciformis, Kappaphycus alvarezii, and Jania rubens with great antioxidant potential significantly increased the oxidative stability of the refined oil.The refined oil supplemented with the ethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Results revealed that the quality of fish oil improved during the refining process. Similar results were also obtained from the sardine oil refining process, exhibiting that FFA, PV, AV, and TOTOX values reduced after the degumming and neutralization process [35,36].…”
Section: Physicochemical Characteristics Of Refined Fob In Degumming ...supporting
confidence: 81%
“…Results revealed that the quality of fish oil improved during the refining process. Similar results were also obtained from the sardine oil refining process, exhibiting that FFA, PV, AV, and TOTOX values reduced after the degumming and neutralization process [35,36].…”
Section: Physicochemical Characteristics Of Refined Fob In Degumming ...supporting
confidence: 81%
“…44 Similarly, Chakraborty reported that the relative percentages of DHA, EPA, and PUFA in refined fish oil were also significantly decreased after 12 days of accelerated storage. 15 Our results indicated that PL containing PUFA decreased more rapidly than TAG containing PUFA, which may be due to the preferential oxidation of PL and the prolonged induction period before oxidation of TAG. 44,45 Moreover, the contents of GPCho and GPEtn containing EPA and DHA in clams were also decreased, which further confirmed the oxidation of PUFA.…”
Section: ■ Discussionmentioning
confidence: 59%
“…Furthermore, previous research related to the changes in n-3 LC-PUFA enriched lipid during accelerated storage has mainly focused on marine fish oils. , The various marine sources of n-3 LC-PUFA differ in terms of their lipid classes. Omega-3 LC-PUFA is present primarily as triacylglycerol (TAG) in fish.…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet–visible (UV–vis) spectroscopic experiments were carried out with a spectrophotometer (Cary 50; Varian, Palo Alto, CA, USA). The fatty acid composition was determined by converting the triglycerides to their saponified products (by 0.5 N KOH/MeOH), and thereafter to their corresponding FAME as described previously (Chakraborty, Joseph, & Joseph, ). FAME and trans ‐fatty acids were characterized by an FID‐based gas chromatograph (AutoSystem XL; PerkinElmer).…”
Section: Methodsmentioning
confidence: 99%